Inspirasi Konservasi Lingkungan Melalui Kegiatan Penghijauan di Sekitar Batalyon Infanteri 761/Ka Warmare Distrik Warmare Kabupaten Manokwari - Evelin A. Tanur; Jonni Marwa; Matheus Beljai; Herik Prasetyawan; Deddy S. Wijaya; Nunang L. May; Descarlo Worabai; Wolfram Y. Mofu; Aditya Rahmadaniarti; Rusdi Anggrianto (I-Com: Indonesian Community Journal, 2024)
ABSTRACT The role of forests as maintaining ecological balance is very important, however, this condition is always influenced by the threat of deforestation and degradation. Both are environmental problems that are a challenge for all regions on Papua Island, including the forests of Warmare District in Manokwari Regency. The threats and challenges of deforestation and forest degradation in the Warmare region could expand significantly if not addressed properly. Therefore, reforestation efforts are needed to minimize these problems. Greening activities were carried out at the TNI Army Complex, Infantry Battalion 761/KA Warmare, Warmare District, Manokwari Regency. The demonstration method used in this activity was planting 1035 plant seeds in prepared locations of 9 types. The 22 participants in this activity came from the Faculty of Forestry and the Indonesian Army Infantry Battalion 761/KA Warmare. Greening activities ran well and smoothly because all participants were able to participate and be actively involved. Keywords: conservation, environment, forest, reforestation, and Warmare.